Monitoring self-reported adherence to antiretroviral therapy in public HIV care facilities in Brazil: A national cross-sectional study. (May 2018) - Santos, Maria Altenfelder; Guimarães, Mark Drew Crosland; Helena, Ernani Tiaraju Santa; Basso, Cáritas Relva; Vale, Felipe Campos; Carvalho, Wania Maria do Espírito Santo; Alves, Ana Maroso; Rocha, Gustavo Machado; Acurcio, Francisco de Assis; Ceccato, Maria das Graças Braga; do Prado, Rogério Ruscitto; Menezes, Paulo Rossi; et al.
Abstract: Introduction: Patient adherence to antiretroviral therapy (ART) is critical for HIV treatment success. Monitoring rates of adherence in public HIV outpatient care facilities can improve outcomes in Brazil where ART is universally available. Methods: We conducted a national cross-sectional survey of ART adherence in 2010. Participants were selected using a multistage probability sample. First, HIV outpatient care facilities were stratified according to 7 Organizational Quality Classification (OQC) groups and regions. Second, 1 or 2 facilities were selected per region for each OQC group. Finally, patients were randomly selected at each facility. In a first component, patients were invited to answer to a web-based questionnaire ( WebAd-Q ), a validated self-reported tool that includes 3 questions on adherence to ART in the past 7 days (time scheduling—timing, drug regimen—medication, and pill counts—dose), herein named indicators of potential nonadherence (IPN). In addition, a subsample of participants were interviewed in order to obtain further data on sociodemographic and clinical characteristics (second component). The proportion of each IPN was estimated using weighted data to account for the sampling design with 95% confidence interval (CI) and descriptive analysis was carried out. Results: Fifty-five facilities were chosen and 2424 patients completed the WebAd-Q in the first component of the study, while 598 patients were interviewed for the second component. The weighted proportions of the IPN were 50.9%, 31.8%, and 19.5%, for timing, medication, and dose, respectively, while11.7% had all 3 indicators, varying from 5.9% in the Southeast and 21.9% in the Northeast regions. Overall, 61.1% of the patients had at least 1 IPN (95% CI: 58.5–63.7%). Patients reporting depression symptoms, illicit drug use and those who missed medical appointments had worse nonadherence outcomes. Conclusions: Overall, there was a high proportion of all indicators IPN and timing was the main component associated with low adherence. Although these indicators may not necessarily indicate individual nonadherence, they represent a worrisome scenario in the public Brazilian HIV care facilities. On a routine basis, these facilities can identify gaps in providing counseling and ART orientation to their clientele and develop innovative strategies to prevent nonadherence.